ANALISIS YURIDIS TERHADAP DISPENSASI KAWIN KARENA HAMIL DI LUAR NIKAH (Studi Putusan Pengadilan Agama Kota Padangsidimpuan Nomor: 7/Pdt.P/2024/PA.Pspk) - Hasibuan, Rosari Damayanti; Ibrahim Siregar; Putra Halomoan Hsb (LPPM STAI Muhammadiyah Probolinggo, 2025)
Marriage regulations establish a minimum age requirement to reduce the prevalence of early marriages, one of which is implemented through the marriage dispensation mechanism. Premarital pregnancy frequently becomes the primary basis for requesting such dispensations, as it is perceived as an urgent circumstance. This study aims to evaluate the effectiveness of legal provisions governing marriage dispensation in the context of non-marital pregnancy. A descriptive empirical-juridical approach was employed, utilizing secondary data from literature review and document analysis of the Religious Court Decision of Padangsidimpuan No. 7/Pdt.P/2024/PA.Pspk, complemented by primary data obtained through interviews with relevant stakeholders. The findings reveal that marriage dispensation due to pregnancy outside wedlock holds legal legitimacy under Article 53 of the Compilation of Islamic Law, which permits marriage without postponement until childbirth. In its ruling, the panel of judges granted the petition while imposing litigation costs of Rp510,000.00 on the applicant. These results underscore that the granting of marriage dispensation requires both valid evidence and the confirmation of an urgent situation.